Diamond-like Cage Motifs in {Cu6(StBu)4} Complexes with Pyridines - Taisiya S. Sukhikh; Maxim N. Sokolov; Pavel A. Abramov (Crystals)
The reduction of Cu(NO3)2 by HStBu in CH3CN under Ar atmosphere produces a light-yellow solution containing numerous {Cux(StBu)y} species. The addition of different pyridines (py-R) into this solution results in the formation of {Cu6(StBu)4} hexanuclear complexes. The slow Et2O diffusion leads to crystals of [Cu6(StBu)4(2-Me-py)5(CH3CN)(NO3)](NO3) (1), [Cu6(StBu)4(Me3py)4(NO3)2]·3.5CH3CN (2a), [Cu6(StBu)4(Me3py)5(NO3)](NO3)·5CH3CN (2b), (NHEt3)[Cu6(StBu)4(CH3CN)3(NO3)3]·H2O (3), [Cu6(StBu)4(2-Br-py)4(NO3)2]·2-Br-Py (4), [Cu6(StBu)4(3-Br-py)6][Cu6(StBu)4(CH3CN)6](NO3)4·9CH3CN (5), and [Cu6(StBu)4(3-Cl-py)6][Cu6(StBu)4(CH3CN)6](NO3)4·5CH3CN (6). The titled compounds were characterized by single crystal X-ray diffraction (SCXRD). The Cu···Cu contacts were analyzed with quantum chemical methods.